Gowaslu Innovation in Improving the Effectiveness of Election Oversight in East Java: Inovasi Gowaslu dalam Meningkatkan Efektivitas Pengawasan Pemilu di Jawa Timur - Waluyo, Ahmad Didit; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2021)
Gowaslu's innovation in increasing the effectiveness of election supervision at the East Java Election Supervisory Board is a form of improving the quality of public services in election supervision through e-government to be effective and efficient. In addition, the creation of an e-government-based Gowaslu application that is used for reporting election violations. So that it makes the community and the East Java Bawaslu to be participatory in responding to it. However, there are still many people who do not know the Gowaslu application and its uses.